EDUKASI MASYARAKAT MENGENAI INOVASI PENGOLAHAN SINGKONG MENJADI KRUPUK PELANGI DI DUKUH PULE DESA PENTUR - Muqorrobin; Muslim Bachtiyar; Ratnawati; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
This journal describes educational and training activities conducted for the community of Dukuh Pule, Pentur Village, focusing on processing cassava into value-added products, specifically rainbow crackers (kerupuk pelangi). The activities aimed to enhance the community’s knowledge and skills in cassava-based food diversification, increase the economic value of local cassava, and introduce a healthy snack alternative that is nutritious and savory. The training covered stages such as cassava selection, dough processing, natural coloring, drying, frying, and packaging of the crackers. The results of the activities showed an increase in community understanding and enthusiasm for developing this processed cassava product